Using mobile application in foreign language learning: a case study (Libellarium: journal for research in the field of information and related sciences, 2017)
The Department of English Language and Literature and the Department of Information Sciences cooperatively, for the purpose of providing additional foreign language training for their students, developed application FFOS Test Your Knowledge (FFOS TYK). TYK was realized as a mobile application for the hybrid development model which allows deployment on multiple platforms. The application is intended primarily for the students of the English language and literature, but it can also be used by other students. The application is available on mobile devices, tablets, laptops and personal computers, and via wireless internet at the faculty students have the free access to it. Each user is given the option for registration and login so that their work can be statistically monitored and ranked. Research data shows that students choose the tests dealing with problem areas, but they prefer shorter tasks when it comes to typing the words. We can conclude that the overall success is rather well distributed with the majority of students scoring around 50% or above with just a few being excellent, and also not many failing to solve the tasks well. The application gives feedback to students and ranks them anonymously. It also offers teachers the possibility to increase the number of questions in the tests and to create the new tests and monitor the success of their students.
Keywords: foreign language learning; e-learning; m-learning; hybrid mobile application development